Improving Al-Imam Al-Mandhari the Hadiths with evidence - Hammad, Nafez Hussain; Abdul-Gafur, Muhammed Ahmad (Arab Journal for Sciences and Research Publishing, 2017)
The research dealt with ashort translation of Imam Zaki al-DinAbi Muhammad Abd al-Azim ibn Abd al-Qawi al- mundhiri. He reveald his method of improving the hadiths with evidence that was agreed upon by al-Bukaari and Muslim or with more than one witness in al Saheehayn. The search also revealed the navigation of Imam al Manzari in modern science and his high accuracy in criticizing the hadiths.